PEMBERDAYAAN GURU DALAM MENGEMBANGKAN PEMBELAJARAN AKTIF MELALUI PEMANFAATAN SUMBER BELAJAR CETAK DAN BERBASIS LINGKUNGAN - Lita Kurnia; Defi Anggrayeni; Robiatul Adawiyah (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2025)
Islamic religious education is an important aspect in the formation of students’ character and morals. There are various Islamic educational institutions, one of which is the madrasah. The role of madrasahs in building national character by instilling religious values as part of the implementation of education in addition to providing general knowledge needs to be considered. Because the implementation of madrasah education has encouraged education in Indonesia to grow. Helping achieve compulsory education, as well as increasing school participation rates in Indonesia. As an integral part of the National Education System (Sisdiknas). Madrasah Takmiliyah Awaliah Al Istiwa is an Islamic religious educational institution located in Babakan Village, RT/RW 02/01, Pabuaran Village, Rangkasbitung District, Lebak Regency, Rangkasbitung. This madrasah has been established since 2004 and has a good reputation in improving the quality of Islamic religious education. The learning process at MTA Khat Al Istiwa uses lecture methods, discussion methods, and practical methods. MTA Khat Al Istiwa offers several flagship programs, including extracurricular activities in calligraphy, khot, and painting. Other programs include Maghrib Quran recitation, women’s religious study, and several other religious activities. This is part of MTA Khat Al Istiwa’s teacher empowerment program, which fosters active learning by utilizing printed and environment-based learning resources.